2017
DOI: 10.1097/gox.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Disability Measures Do Not Correlate with Electrodiagnostic Severity in Carpal Tunnel Syndrome

Abstract: Background:Electrophysiologic studies including electromyography and nerve conduction studies play a role in the evaluation of carpal tunnel syndrome (CTS), despite evidence that these studies do not correlate with CTS-specific symptom scores. There is a lack of evidence comparing electrophysiologic data with general measures of function.Methods:Fifty patients presenting for CTS treatment over an 8-month period were analyzed retrospectively. All patients completed surveys including the Quick Disabilities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The correlation between Quick-DASH scores and electrodiagnostic findings is not statically significant (r = -0.18, P = .08). 276…”
Section: IIImentioning
confidence: 99%
“…The correlation between Quick-DASH scores and electrodiagnostic findings is not statically significant (r = -0.18, P = .08). 276…”
Section: IIImentioning
confidence: 99%
“…The Boston scale has been shown to be responsive to change after treatment, but has not been validated to serve as the threshold between specific severity levels (Atroshi et al., 2006; Gerritsen et al., 2002; Leite et al., 2006). Similarly, patient symptoms, electromyography, and nerve conduction studies have not been found to correlate with patient overall well-being (Tulipan et al., 2017). In fact, recent studies are contesting the notion that surgery be reserved solely for patients with severe CTS, especially when considering cost-utility ratios (Ono et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bakhsh et al 4 found no significant correlation between DASH or BCTQ scores and electrodiagnostic results in a cohort of 48 patients with a primary diagnosis of CTS. Similarly, Tulipan et al 25 evaluated electrophysiologic severity in 50 patients with CTS who completed DASH and found no correlation between degree of median neuropathy and patient-reported symptom severity. The poor correlation between PROs and electrodiagnostic severity is in part due to variability among sensory and motor values, which complicates the achievement of a consensus.…”
Section: Discussionmentioning
confidence: 99%